Feasibility assessment of alternative supply chain designs: the case of Cargill Animal Nutrition - Anderson, Katlin R. (Kansas State University, 2014)
Cargill Animal Nutrition is a global manufacturer and distributor of animal nutrition products. They operate in the United States through 6 separately managed regions that control a number of facilities throughout the entire United States. Cargill Animal Nutrition Southeast Region manages a network of eleven plants and two warehouses in the southeast part of the United States. The purpose of this thesis is to explain the current supply chain design including the relationships that exists between facilities, analyze the costs associated with the current design and relationships, and assess the feasibility of alternative designs of supply chain strategies available. A brief description of each facility along with production characteristics specific to each facility is given. Due to certain production characteristics, dependent relationships exist between certain plants. These relationships create restrictions to which our supply chain is subject. Other relationships are not as rigid and thus can be manipulated in pursuit of lowering overall supply chain costs. The model resulting from this thesis will facilitate the assessment of the feasibility of these changes. There are many costs associated with the supply chain; however, costs included in this analysis are limited to the costs that could vary when changing suppliers. The price of the product, transportation costs, and certain warehouse fees deemed relevant to this research are applied to the expected annual sales tons to reach a total cost of supply chain considering the assumptions made. The base scenario was defined according to known facts regarding the current design of our supply chain, which included identification of suppliers, supplier prices, transportation costs, and associated handling/warehouse fees, as well as determining the quantity of product that would need to flow throughout our supply chain. Then the total cost associated with the current supply chain design was assessed according to our analytical model. Once the total cost of the base scenario was determined, comparison to alternative scenarios could take place. Changing the relationships between locations of the supply chain results in alternative scenarios to which the analytical model and decision rule developed can be applied to determine feasibility of the alternative supply chain designs. Operating within the confines of the research, the total cost of the current supply chain design was determined to be $15,697,426. That total cost then serves as a base figure which can be used in comparison with the overall cost of alternative scenario #1. Scenario #1 resulted in a total cost of $15,447,597 – an annual savings of $249,828. Scenarios #2 through #4 were evaluated against the total cost of scenario #1. The total cost of scenario #2 is $15,421,364 which results in annual savings of $26,234. Scenario #3 results in a total supply chain cost of $15,347,888 which equates to annual savings of $9,710 in comparison to scenario #1. The final scenario in this study results in a total cost of $15,443,547. The annual savings generated by scenario #4 in comparison to scenario #1 are $4,050. The results indicate that there are alternative configurations of Cargill Animal Nutrition’s Southeast supply chain that can be developed to increase the competitiveness of operations and improve operational excellence through cost savings. These results are used to inform management in the implementation of the new goals that have been established for the organization. Further utilization of the tool developed will result in increased knowledge of the costs associated with supply chain design. This will allow the company to be able to understand the cost of their supply chain so they can benefit from decreased supply chain costs by reacting to changing market factors.
Keywords: Supply chain management; Animal nutrition; Cargill; Business (0310); Economics (0501)